Electrocardiographic, echocardiographic and heart biomarker parameters in sheep experimentally poisoned by Palicourea marcgravii (Rubiaceae) - Isabelle M. Cunha; Daniel A.B. Lessa; Vivian A.N. Carvalho; Nayro X. Alencar; André L.S. Teixeira; Marina G. Chenard; Guilherme N. Souza; Michel J.SA. Helayel (Pesquisa Veterinária Brasileira, 2022)
ABSTRACT: The present study aimed to identify and describe cardiac alterations in sheep experimentally poisoned with Palicourea marcgravii through analysis of serum cardiac biomarkers (serum troponin I and creatine kinase - CK-MB) and electro and echocardiographic assessments to contribute to a better understanding of the poisoning pathophysiology. P. marcgravii is the main plant within a group of 22 species that cause sudden death in Brazil; its toxic principle is sodium monofluoroacetate. Eight healthy crossbreed male sheep, aged between five and twelve months, weighing 14 to 27kg, were evaluated. The animals received 1g kg-1 of P. marcgravii plants orally. The sheep were evaluated before administering the plant (T0) through electro and echocardiography and blood collection to assess cardiac biomarkers (CK-MB and cTnI). Collections and analyses were repeated every four hours until the animal’s death. During the study, there was the presence of extravasation of serum troponin I carried out in a qualitative test, with positive values at time T4, and the serum CK-MB biomarker had a peak at T4 and slightly decreased at T8. The electro and echocardiographic examinations showed that the cause of death in these animals was due to acute heart failure characterized by arrhythmias, tachycardia/ventricular fibrillation, drop in cardiac output, left ventricular (LV) systolic dysfunction by the progressive decrease in the LV ejection fraction (EF), decrease in LV fractional shortening (FS), and decrease in aortic flow velocity and aortic flow gradient. This study seems to be the first to evaluate cardiac alterations in sheep poisoned by P. marcgravii through cardiac biomarkers and electro and echocardiographic exams.